Genetic and phylogenetic characterization of novel bocaparvovirus infecting chimpanzee - Brožová, Kristýna; Hrazdilová, Kristýna; Slaninková, Eva; Modrý, David; Černý, Jiří; Celer, Vladimír (Infection, genetics and evolution, 2016)
Primate bocaparvoviruses were first described in 2005, since then further human and gorilla bocaparvoviruses have been identified. To uncover diversity of non-human primates' bocaparvoviruses, their phylogenetic relationship and potential to cross the host species barrier, we tested 153 fecal samples from 17 captive primate species. The only one captive female of central chimpanzee (coded CPZh2) has been identified as bocaparvovirus positive. Based on the full genome phylogenetic analyses, CPZh2 strain shows close relationship to HBoV3 and GBoV. Further recombination analysis confirmed expected mosaic origin of CPZh2 strain. According the phylogenetic position, following the ICTV recommendations, we propose a novel genotype within the Primate bocaparvovirus 1 species infecting chimpanzee.
Keywords: Bocavirus; Recombination; Animals; Genome, Viral; Female; Genotype; feces; Feces; ženské pohlaví; genom virový; infekce viry z čeledi Parvoviridae; Parvoviridae Infections; genotyp; Bocaparvovirus; Evolution, Molecular; molekulární evoluce; Phylogeny; Recombination, Genetic; Pan troglodytes; Chimpanzee; Primate; nemoci lidoopů; Sequence Analysis, DNA; Ape Diseases; zvířata; sekvenční analýza DNA; fylogeneze; rekombinace genetická